The Influence of The Project Based Learning (PJBL) Learning Model Assisted by Videoscribe Media on The Creativity of Learning Dance Arts - Rafiq Muhammad Mughni; Elok Fariha Sari (Postgraduate, University of Mataram, 2024)
In supporting the development of students' creativity, teachers need to implement models and media in learning that can foster a spirit of creativity. Additionally, enhancing students' creativity will serve as a response to the challenges of 21st-century learning, where higher-order thinking skills are essential.The purpose of this research is to determine the effect of the project based learning (Pjbl) learning model assisted by Videoscribe Media on the creativity of dance learning in grade 4 students at SDN 1 Teluk Kulon, Jepara District. The research method used is a quantitative research method using a pre-experimental design model using the One Group Pretest-Posttest Design pattern and tested statistically using the Wilcoxon test. Before implementing the project based learning (Pjbl) learning model assisted by Videoscribe Media, the results of creativity in learning dance obtained an average score of 62.72, but after implementing the project based learning (Pjbl) learning model assisted by Videoscribe Media, the results of creativity in learning dance obtained an average score. -average is 81.75. Based on these results, it can be concluded that there is an influence of the project based learning (PjBL) learning model and Videoscribe Media on the creativity of learning dance among students at SDN 1 Teluk Kulon, Jepara Regency.